Differences in Use of High-quality and Low-quality Hospitals Among Working-age Individuals by Insurance Type. Issue 2 (February 2017) - Popescu, Ioana; Heslin, Kevin C.; Coffey, Rosanna M.; Washington, Raynard E.; Barrett, Marguerite L.; Karnell, Lucy H.; Escarce, José J.
Abstract : Background: Research suggests that individuals with Medicaid or no insurance receive fewer evidence-based treatments and have worse outcomes than those with private insurance for a broad range of conditions. These differences may be due to patients' receiving care in hospitals of different quality. Research Design: We used the Healthcare Cost and Utilization Project State Inpatient Databases 2009–2010 data to identify patients aged 18–64 years with private insurance, Medicaid, or no insurance who were hospitalized with acute myocardial infarction, heart failure, pneumonia, stroke, or gastrointestinal hemorrhage. Multinomial logit regressions estimated the probability of admissions to hospitals classified as high, medium, or low quality on the basis of risk-adjusted, in-hospital mortality. Results: Compared with patients who have private insurance, those with Medicaid or no insurance were more likely to be minorities and to reside in areas with low-socioeconomic status. The probability of admission to high-quality hospitals was similar for patients with Medicaid (23.3%) and private insurance (23.0%) but was significantly lower for patients without insurance (19.8%, P <0.01) compared with the other 2 insurance groups. Accounting for demographic, socioeconomic, and clinical characteristics did not influence the results. Conclusions: Previously noted disparities in hospital quality of care for Medicaid recipients are not explained by differences in the quality of hospitals they use. Patients without insurance have lower use of high-quality hospitals, a finding that needs exploration with data after 2013 in light of the Affordable Care Act, which is designed to improve access to medical care for patients without insurance. Abstract : Supplemental Digital Content is available in the text.